Comparison of the Effects of a Combination of Centella asiatica and Mentha piperita Leaf Extracts on the Number of Normal Brain Cells in Male Mice (Mus musculus) - Padmiswari, Anak Agung Istri Mas; Antari, Ni Wayan Sukma; Gandamayu, Ida Bagus Maha; Adiana, I Nengah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Chronic stress is known to cause neuronal damage in the hippocampus, particularly in the CA1 and CA3 areas, which play a crucial role in memory and learning. One way to prevent this damage is by using natural ingredients with neuroprotective properties. This study aimed to compare the effects of Centella asiatica and Mentha piperita leaf extracts, either singly or in combination, on the number of normal neurons in the hippocampus of male mice exposed to stress. Twenty-five male mice were divided into five treatment groups: K− (control without treatment), K+ (stress without extract), P1 (stress + Centella asiatica extract), P2 (stress + Mentha piperita extract), and P3 (stress + combination of Centella asiatica and Mentha piperita). Stress was induced using a restraint stress method, while the extracts were administered orally at the prescribed dosage. After the treatment period, the hippocampus was removed, and histological slides were prepared with Hematoxylin-Eosin staining to count the number of normal neurons in the CA1 and CA3 areas. The results showed that the K+ group experienced a significant decrease in the number of normal neurons compared to the K− group. Administration of gotu kola (P1) and mint (P2) extracts increased the number of neurons compared to K+, but not to the same extent as K−. The combination of Centella asiatica and Mentha piperita extracts (P3) showed the most optimal effect, with the number of normal neurons approaching that of the negative control group. These findings indicate that the combination of Centella asiatica and Mentha piperita has synergistic potential in protecting hippocampal neurons from stress-induced damage. Further research is needed to explore the molecular mechanisms underlying this neuroprotective effect.